Toksisitas Biji Srikaya (Annona Squamosa) terhadap Sitophilus sp. Pada Beras - Atikah, Putri Dela; Subagiya, Subagiya; Sulistyo, Ato (Universitas Sebelas Maret, 2018)
Sitophilus sp. is one of warehouse pests that can result in damage in the rice stored. The damage induced by Sitophilus sp. or weevil reaches 5-10% of material stored. One integrated way of controlling pest (integrated pest control, thereafter called IPC) that can control Sitophilus sp. is to use organic insecticide made of Annona (Annona squamosa) seeds. This research aimed to find out the annona seed dose effective in controlling Sitophilus sp. and the effect of annona seed administration on rice quality. This research employed experimental method with Completely Random Design. The treatment given included the following doses 0 gram, 1 gram powder, 3 gram powder, 5 gram powder, 1 gram grain, 3 gram grain, and 5 gram grain in 50 gram rice. Every treatment was repeated 4 times, so that there were 28 experiment units. Research variables were mortality, efficacy, toxicity, material weight shrinkage, rice color and aroma. The result of research showed that the effective doses were 3 and 5 gram powder of annona seed with mortality of 98.93%, efficacy of 100%, high toxicity, low rice weight shrinkage, color produced was turbid white to brownish, and not resulting odor in rice.